(Extra)ordinary portraits: Self-representation, public culture and the contemporary British soldier. (April 2016) - Parry, Katy; Thumim, Nancy
This article explores the contemporary image of the British soldier, especially where the opportunity for soldiers to tell their own stories is highlighted as the core justification in the presentation of co-produced materials. The authors consider the particular generic affordances, constraints and aesthetics of two recent projects, Our War (BBC 3) and War Story (Imperial War Museum), both of which hope to offer a 'direct' insight into soldiers' experiences in Afghanistan, albeit through the lenses of public institutions which inevitably come with their own interpretive frameworks. At the heart of the study are the concept of self-representation and the idea of the portrait. The article examines recurrent themes, styles of portrayal and notable absences, asking, for example: how do the different dimensions of mediation constitute the soldiers as 'ordinary' and 'extraordinary'? The authors argue that it is theoretically and empirically productive to analyse the two projects together as interconnected forms of a 'genre of self-representation'.